The menu of autocratic innovation. Issue 6 (17th August 2020) - Morgenbesser, Lee
ABSTRACT: This article develops the menu of autocratic innovation to account for a perceived transformation in the nature of autocratic rule. Drawing from an original list of 20 techniques intended to cultivate the pretence of accountability without permitting the actual practice of it, the article describes how autocratic innovation takes different forms (informational, legal, political, reputational and technological) and concerns different targets (citizens, civil society activists, opposition members and foreign policymakers). This theoretical framework is tested against nine autocratic regimes in Southeast Asia from 1975 to 2015. The evidence shows substantial variation in terms of the form and target of at least six distinct techniques: libel and defamation suits, anti-civil society measures, mock compliance to human rights agreements, public relations firms, think tanks and zombie monitors. The article concludes by discussing three possible explanations for why autocratic innovation occurs: waves of autocratization, density of international linkages and leadership turnover.